Biogas from Poultry Manure - Berbić, Medina; Avdić, Nurudin (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2016)
It is estimated that around 2 billion of waste annually is formed in the European Union (EU), which is deposited-in sanitary and industrial dumps, and it is recorded continuous increasing in the production of organic waste. Biodegradability of organic substances enables the emission of CH4 (biomethane) that has 25 times higher the greenhouse potential than CO2 as a predominant greenhouse gas in the atmosphere. The treatment of organic waste through anaerobic digestion flourished in the 20th century, thus opening the way to the environmental remediation of manure, as one of the most influential source of methane emissions. This study research the production of methane in poultry manure, as one of the most usual animal fertilizers in Bosnia and Herzegovina. The research activities are comprised of waste characterization and testing the biodegradability of waste using Biomethan Potential Test BMP. The temperature range of the study was 37 ± 1°C (mesophilic process). The research topic is manure of laying hens, without bed. The conducted research activities have shown the existence of possibilities for the production of biogas by using anaerobic biological treatment of poultry manure. The yield of biogas in the amount of 5752 mL was achieved with a methane content of 53.19% for the treatment of the substrate with 15% total solid (TS). By treating the substrate with 17% total solid (TS) less biogas is obtained, in the amount of 2337.50 mL of biogas but with a higher content of methane, in the amount of 56.36%. Physico-chemical analysis revealed a deviation ratio of C(COD):N:P:S from the optimal ratio for substrate and digestate, which caused disturbances in the performance of the anaerobic digestion process. Inadequate ratio is expressed with low carbon content and a high content of nitrogen and sulfur. The course of the study has proven to be extremely useful for testing the possibilities of biogas production in combination with other organic waste, which opens up opportunities for further research.